BEYOND RELIGION AND ETHNICITY: Sit-At-Home and Freedom Agitations among the IGBO in South-Eastern Nigeria - Ugochukwu Obumneme Ezewudo; Ikeagwuchi Ikechukwua Ukwuoma; Favour Chukwuemeka Uroko (MAHABBAH: Journal of Religion and Education, 2022)
The concept of "sit-at-home" is a recent term used by freedom agitators, particularly of Igbo extraction, to get the attention of the Nigerian government to grant sovereignty to the Indigenous people of Biafra. It is also a concept that challenges the authority of the government while asking it to end marginalisation and to release the leader of IPOB, Nnamdi Kanu, who was arrested and is presently in the custody of the Department of State Services (DSS). Sit-at-Home, particularly in Anambra, Enugu, Imo, Abia, and Ebonyi (South-Eastern states of Nigeria), has been given socio-political interpretation. Generally, politics is supposed to be the machinery for resolving conflict and governing the people sincerely. Unfortunately, it has become an agent of disunity in the Nigerian state. This has led to several agitations in the past, but they are more vocal in present times. The agitations for freedom have often triggered violence and conflict between the government and the freedom agitators, given room for the marginalisation of certain regions, and consequently proved Nigeria's government's inability to decide on behalf of the governed. The methodology used in the study is a qualitative phenomenological method. The study examines the challenges and implications of the concept for the socio-economic, socio-political, socio-cultural, and socio-religious lives of the people of southeastern Nigeria. The paper observes that this face-off could be resolved if the needs of the Igbo were critically examined and attained. The paper calls on the government to organise a dialogue and a referendum in order to end the menace in the South-Eastern region.